Implementasi Pembelajaran Baca Tulis Al-Qur’an dengan Metode Iqro pada Anak Usia Dini Di RA Raudhatush Shibyan - ade imun romadan imun (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2021)
The research aims to know how to read and write the application of the Al Quran with Iqro methods in early childhood and the factors that support and impede learning to read and write the Qur’an. This research is a qualitative descriptive which examines data quality (concepts, thoughts and actions) and describe what it is. The results of learning to read and write first research Al-Qur’an with methods Iqro prepared in a planned and systematic based on the curriculum RA. Secondly, there is a supporting factor in the application of methods Iqro is the availability of books, media, and other learning tools that support this learning process. Their infrastructure and tenacity educators in the implementation of learning. While the inhibiting factors such as lack of training on a regular basis for the application of methods for Teachers Iqro RA. Still, their parents are less attentive to the children in learning Al-Qur’an.